FORMS OF COLLABORATION BETWEEN TEACHERS AND PARENTS IN GUIDING THE RELIGIOUS AND MORAL EDUCATION OF STUDENTS AT RUMAH QUR'AN AL-HAZIQ BATANG KUIS - Siagian, Uli Ramadani; Fatkhur Rohman (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the form of cooperation between ustadzah and parents in guiding the worship education and morals of students at Al-Haziq Qur'an House in Batang Kuis. The focus of the problem is how the form of cooperation between ustadzah and parents in guiding the worship and moral education of students, what are the factors that influence it (supporting and inhibiting factors), and how the impact of this cooperation on the worship and moral education of students. The research used descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The data analysis technique uses the theory of Miles and Huberman with data reduction, data presentation, and conclusion drawing. The results showed that the form of cooperation was realized in routine communication through WhatsApp groups, mutaba'ah books, and santri guardian meetings, worship assistance at home, and parental involvement in institutional activities. Supporting factors include a common vision of education, exemplary ustadzah and parents, and the use of digital media. The inhibiting factors found are the limited time of parents due to their busy work schedules, the lack of two-way communication, and the tendency of some parents to leave full guidance to the ustadzah. Good cooperation has a positive impact on the discipline of worship, the fluency of memorization, and the formation of santri morals, while the lack of parental support causes the development of the students.